A study of Pulmonary Manifestations in Collagen Vascular Diseases - Parul Vadgama; Pankaj Garg (Medsci Publications, 2018)
Introduction: Collagen vascular diseases are group of diseases with specific characteristics. Pulmonary manifestations are com- monly present in collagen Vascular Diseases. The research was conducted to study pulmonary manifestations of collagen vascular diseases clinically; to study the demographic incidence in patients with pulmonary manifestations in collagen vascular diseases; to study radiological manifestations in terms of Chest X-Ray & HRCT Thorax; and also to study pulmonary functions tests in collagen vascular diseases. Material & methods: This is a retrospective study on 50 patients of already diagnosed patient collagen vascular diseases. Results: Pulmonary manifestations are present in 40% of patients had scleroderma (SC), 30% of cases of Systemic Lupus Erythematosis (SLE), 20% of patients of Rheumatoid Arthritis while 10% of Patients with Mixed Connective Tissue Disorders. Restrictive pattern is common in all types of collagen vascular dis- eases on pulmonary function testing. 24% of patients of collagen vascular disease had pulmonary arterial hypertension. On HRCT reticulonodular pattern is more common. Conclusion: Pulmonary manifestations are commonly present in collagen vascular diseases. Broad choice of investigations should be done to prevent early mortality & morbidity.